1975
DOI: 10.1021/ac60359a010
|View full text |Cite
|
Sign up to set email alerts
|

Reactor-separator membrane combining immobilized urease and an anion exchange membrane

Abstract: The reactor-separator membrane was prepared by molding a urease gel layer directly onto a commercial anion exchange membrane. When this two-layer membrane was used as a barrier between donor urea and acceptor buffer solutions, product ammonium ion was enriched in the acceptor solution up to a hundredfold over donor ammonium ion levels during a thirty-minute reaction period. The rate of product ammonium ion buildup was linear with time and was found to be proportional to initial donor substrate concentration ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Although this is not strictly an "enzyme electrode", but rather a microflow system, it does provide the advantage that the electrode membrane is not in contact with the solution and therefore does not (62) become clogged. Recent work by Blaedel and Kissel in which a urease membrane was joined to an anion-exchange membrane indicates that the selectivity problem of the cation NH4+ selective electrode might be avoided by using the electrostatic exclusion phenomena of an ion-exchange material (94). Their work demonstrates the powerful advantages inherent in the use of membrane technology for simultaneous separation and detection.…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Although this is not strictly an "enzyme electrode", but rather a microflow system, it does provide the advantage that the electrode membrane is not in contact with the solution and therefore does not (62) become clogged. Recent work by Blaedel and Kissel in which a urease membrane was joined to an anion-exchange membrane indicates that the selectivity problem of the cation NH4+ selective electrode might be avoided by using the electrostatic exclusion phenomena of an ion-exchange material (94). Their work demonstrates the powerful advantages inherent in the use of membrane technology for simultaneous separation and detection.…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…Although this is not strictly an "enzyme electrode", but rather a microflow system, it does provide the advantage that the electrode membrane is not in contact with the solution and therefore does not for serum glucose (62) become clogged. Recent work by Blaedel and Kissel in which a urease membrane was joined to an anion-exchange membrane indicates that the selectivity problem of the cation NH4+ selective electrode might be avoided by using the electrostatic exclusion phenomena of an ion-exchange material (94). Their work demonstrates the powerful advantages inherent in the use of membrane technology for simultaneous separation and detection.…”
Section: Cosh Axmentioning
confidence: 99%
“…From the open literature, it is found that most of the published mathematical models were unable to capture the coupled biochemo-electromechanical behavior of the hydrogel. For example, the published mathematical models were inadequate in predicting the volumetric behavior of the hydrogels in response to the urea, where the simulated diffusion and reaction of the reactive solutes were associated with the urea hydrolysis and not the concomitant mechanical behavior of the hydrogels (Blaedel and Kissel, 1975;Chen and Chiu, 2000), including Moynihan et al (1989) and Chowdhury and Bhattacharya (1997), where they modelled the kinetic parameters of the urea-sensitive hydrogel via the mass balance and Michaelis-Menten equations.…”
Section: Introductionmentioning
confidence: 99%